2008
DOI: 10.1097/brs.0b013e318190affe
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Complications of Combined Anterior and Posterior Cervical Decompression and Fusion Crossing the Cervico-Thoracic Junction

Abstract: Complications are frequent following these procedures, although the majority were minor and resolved without lasting effect. Airway edema requiring prolonged intubation or reintubation was frequent. With the numbers available, we were unable to show a relationship between the need for extended intubation and variables including operative time, blood loss, or volume of fluid replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 21 publications
2
41
0
1
Order By: Relevance
“…Anterior surgical strategies are increasingly recognized as advantageous for multilevel cervical decompression of the anteriorly compromised spinal cord, providing the ability for anterior release, durable reconstruction of physiologic alignment and instrumented fusion through a less traumatic approach compared to the posterior neck dissection [3,6,20,37,38,40,[45][46][47]55]. With anterior procedures, decompression of the neurologic structures can be accomplished by means of segmental discectomy or partial corpectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Anterior surgical strategies are increasingly recognized as advantageous for multilevel cervical decompression of the anteriorly compromised spinal cord, providing the ability for anterior release, durable reconstruction of physiologic alignment and instrumented fusion through a less traumatic approach compared to the posterior neck dissection [3,6,20,37,38,40,[45][46][47]55]. With anterior procedures, decompression of the neurologic structures can be accomplished by means of segmental discectomy or partial corpectomy.…”
Section: Introductionmentioning
confidence: 99%
“…In studies investigating combined anterior-posterior cervical procedures, Hart el al. 8 and Aryan et al 1 reported dysphagia rates of 46% and 19%, respectively. Although all cases of dysphagia with follow-up data in our study resolved subjectively by 12 months, there is morbidity associated with such complications; 61.5% and 38.5% of the cases required NG and PEG tube placement, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This approach may be properly extended to expose T3-T4 in accordance with the need of the condition of patients, and it partially splits the sternum and does not enter the thoracic cavity so that respiratory or circulatory systems are less disturbed and fewer postoperative complications appear. For the anterior operation, selecting a left approach or right approach has no significant difference for the surgeon to operate; however, because during the operation the distal vertebral body is usually unclearly exposed and needed long traction, postoperative recurrent laryngeal nerve injury easily appears and the literature reports that the incidence is as high as 46 % [21]. At the fourth thoracic vertebra level, the left recurrent laryngeal nerve travels into the tracheoesophageal groove from the upper thoracic outlet and during the traction process it is not easily damaged, therefore, the use of the left approach is more reasonable than the right one.…”
Section: Discussionmentioning
confidence: 97%